Computational Chemistry; A Useful Tool for the Chemical Synthesis of Complex Molecules, Heterocycles and Catalysts - Arrieta, Ana; de la Torre, María C.; de Cózar, Abel; Sierra, Miguel A.; Cossío, Fernando P. (Synlett, 2013)
This Account describes our recent studies on the chemical synthesis of cyclic, densely substituted molecules by means of a hybrid approach consisting of the synergistic interaction between computational and experimental chemistry. In addition, two related total syntheses of complex molecules (±)-Scopadulin and (–)-Exiguolide are presented as case studies in which computational chemistry can be used to detect and, eventually, avoid potential failures involving key transformations of advanced intermediates.1 Introduction2 Computational Treatment of Molecules3 Computational Characterization of Reactants, Reaction Intermediates, Products and Transition Structures4 Computational–Experimental Analysis of the Stereocontrol in Thermal Pericyclic Reactions4.1 Concerted and Stepwise [3+2] Cycloadditions4.2 Concerted and Stepwise [8+2] Cycloadditions5 Total Synthesis of Complex Molecules; Two Case Studies5.1 Total Synthesis of (±)-Scopadulin5.2 Total Synthesis of (–)-Exiguolide6 Conclusions and Outlook
Keywords: pericyclic reactions; cycloaddition; asymmetric catalysis; antitumor agents; metathesis; Michael addition; ring closure; ylides